Analisa Hubungan Antara Intensitas Persaingan, Ukuran Perusahaan, dan Organisasi Pembelajaran Terhadap Penggunaan Sistem Informasi Akuntansi Pada Sektor Hotel di Surabaya - Chandra, Novianto (Business Accounting Review, 2013)
Year to year, hotel industry showed a positive in increasing number of customer. Therefore, this topic was chosen based on nowadays reality which is the increasing in market competition in hotel industry, so that business person needs high quality informations. One of the purpose of accounting information system is to deliver a high quality informations for decision making purposes. This study aimed to examine the relationships between intensity in market competition, corporate size, and learning organization to usage of accounting information system (AIS) in hotel in Surabaya. Samples used in the study were 90 hotelsâ manager or owner in Surabaya. The hypothesis is tested by using Product Moment correlation method. The result of this testing indicated that all three variables including intensity in market competition, corporate size, and learning organization has significant relationship with the usage of AIS in hotels. Corporate size used in this study was the measurement of non-financial. In addition, research results showed that the highest usage of AIS in hotel industry is the provision of information for tax purposes.